Traumatic common hepatic artery injury causing isolated right hepatic ischemia due to a left accessory artery. A case report() - Fernandes, Eduardo (Int J Surg Case Rep, 2017)
INTRODUCTION: Hepatic arterial liver flow is renowned for its redundancy. Previous studies have demonstrated that the common hepatic artery is not essential for liver survival. We present a case of a 31year-old involved in a high-speed motor vehicle accident whose liver survived thanks to the presence of an accessory hepatic artery. PRESENTATON OF THE CASE: We present the case of a 31year-old male who sustained a traumatic injury of the proper hepatic artery following a motor vehicle accident. The patient suffered temporary right liver lobe ischemia due to the presence of an accessory left hepatic artery. This resulted in the selective formation of ‘biliary lakes' distinctively within the territory of the right hepatic artery supply. Simultaneously the patient developed a pseudo-aneurysm of the proper hepatic artery which required radiology intervention. At the time of pseudo-aneurysm embolisation, a rich network of arterial collaterals had formed between the accessory left hepatic and the inferior phrenic artery. On follow up the biliary lakes to the right lobe had resolved, but a small area at the periphery of the right lobe had encountered atrophy. DISCUSSION: This case report is an ‘in vivo’ demonstration of liver resilience to arterial flow re-distribution and demonstrates the ability of the biliary epithelium to recover from and ischemic injury. CONCLUSION: Parenchymal liver survival is mostly independent from flow within the common hepatic artery. Acute and chronic liver parenchyma changes following interruption of hepatic artery flow can still occur.